Evaluation of the Impact of Using Technology in Physical Education Learning at Serambi Mekkah University - Suardi (International Journal Education and Computer Studies (IJECS), 2023)
This research aims to evaluate the impact of using technology in Physical Education learning in the Serambi Mekkah University environment. To integrate technology in the Physical Education curriculum, this research identifies its potential impact on student participation, achievement of learning outcomes, and improvement of physical well-being. The research method involved a literature review to detail the theoretical foundation, a needs analysis to understand the status of the Physical Education program at the university, and the implementation of technology-based interventions in learning. This research makes a significant contribution to the understanding of the effectiveness of applying technology to improve Physical Education learning, especially in the context of Serambi Mekkah University. Data collected through surveys, interviews and observations will be analyzed comprehensively to evaluate the effectiveness of the technology integration. It is hoped that the results of this research can provide valuable insight for the development of better learning policies and practices in supporting physical education, health, and recreation in higher education environments. Through an in-depth understanding of the impact of using technology in Physical Education learning, it is hoped that this research can provide concrete and effective recommendations for improving the quality of physical education at Serambi Mekkah University. As a higher education institution, the implementation of technology in the learning process can be the key to stimulating student engagement, increasing understanding of Physical Education concepts, and strengthening aspects of physical well-being. Therefore, it is hoped that the findings from this research will pave the way towards the development of innovative learning policies and strategies at university level, as well as stimulate further discussion about the role of technology in physical education.